Wie die Berichte über die menschliche Entwicklung die Welt verändern - JOSHI, Devin K. (Institutional Knowledge at Singapore Management University, 2015)
Through the reports on human development (HDR), the United Nations Development Programme (UNDP) promotes the idea of "human development" for 25 years. The concept human development aims to empower people to live full and independent lives. To find out if the understanding of development has changed through the HDRs, academic and media coverage of the HDRs based on qualitative and quantitative content analyzes were evaluated. It turns out that the media regularly and refer mostly positive in all parts of the world to the reports.